2019
DOI: 10.1111/jspn.12284
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in adolescents with sickle cell disease: The influence of caregiver health literacy

Abstract: Purpose After patients with sickle cell disease (SCD) transfer from pediatric care to adult care, significant morbidity and mortality occurs. There are many possible contributors to the success or failure of this transition. One hypothesis is that health literacy influences this transition from pediatric to adult health care. The purpose of this study was twofold: (a) to examine the relationship between caregiver and adolescent health literacy levels in adolescents with SCD; and (b) to further describe individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Interestingly, several studies have reported no association between adolescent and caregiver health literacy. 55,56 These findings suggest that patient-specific skills, which likely include neurocognitive abilities, are the best predictor of health literacy.…”
Section: Health Literacymentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, several studies have reported no association between adolescent and caregiver health literacy. 55,56 These findings suggest that patient-specific skills, which likely include neurocognitive abilities, are the best predictor of health literacy.…”
Section: Health Literacymentioning
confidence: 93%
“…These results suggest that adolescents with poor health literacy may be especially vulnerable to difficulties with IADL skills that rely on calculation, including management of medications and finances. Interestingly, several studies have reported no association between adolescent and caregiver health literacy 55,56 . These findings suggest that patient‐specific skills, which likely include neurocognitive abilities, are the best predictor of health literacy.…”
Section: Functional Implications Of Neurocognitive Deficitsmentioning
confidence: 93%
“…It has recently been postulated that these difficulties during transition could be influenced by health literacy (Caldwell, 2019(Caldwell, , 2020Perry et al, 2017). Health literacy is defined as "the degree to which individuals have the capacity to obtain, process and understand basic health information and services needed to make appropriate health decisions" (Ratzan & Parker, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have evaluated some of the influencing factors on the health literacy of adolescents with SCD (Caldwell, 2019; Caldwell & Melton, 2020; Perry et al, 2017). This previous literature found that age, current grade level, and income play an influencing role on the health literacy of adolescents with SCD (Caldwell, 2019; Perry et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have evaluated some of the influencing factors on the health literacy of adolescents with SCD (Caldwell, 2019; Caldwell & Melton, 2020; Perry et al, 2017). This previous literature found that age, current grade level, and income play an influencing role on the health literacy of adolescents with SCD (Caldwell, 2019; Perry et al, 2017). There was, however, no relationship between adolescent health literacy and (1) caregiver health literacy or (2) the presence of neurologic deficits in the previously evaluated samples (Caldwell & Melton, 2020; Perry et al, 2017).…”
Section: Introductionmentioning
confidence: 99%